Mutational Analysis of Mammalian Translation Initiation Factor 5 (eIF5): Role of Interaction between the β Subunit of eIF2 and eIF5 in eIF5 Function In Vitro and In Vivo - Das, Supratik (American Society for Microbiology, 2000)
Eukaryotic translation initiation factor 5 (eIF5) interacts with the 40S initiation complex (40S–eIF3–AUG–Met-tRNA(f)–eIF2–GTP) to promote the hydrolysis of ribosome-bound GTP. eIF5 also forms a complex with eIF2 by interacting with the β subunit of eIF2. In this work, we have used a mutational approach to investigate the importance of eIF5-eIF2β interaction in eIF5 function. Binding analyses with recombinant rat eIF5 deletion mutants identified the C terminus of eIF5 as the eIF2β-binding region. Alanine substitution mutagenesis at sites within this region defined several conserved glutamic acid residues in a bipartite motif as critical for eIF5 function. The E346A,E347A and E384A,E385A double-point mutations each caused a severe defect in the binding of eIF5 to eIF2β but not to eIF3-Nip1p, while a eIF5 hexamutant (E345A,E346A,E347A,E384A,E385A,E386A) showed negligible binding to eIF2β. These mutants were also severely defective in eIF5-dependent GTP hydrolysis, in 80S initiation complex formation, and in the ability to stimulate translation of mRNAs in an eIF5-dependent yeast cell-free translation system. Furthermore, unlike wild-type rat eIF5, which can functionally substitute for yeast eIF5 in complementing in vivo a genetic disruption of the chromosomal copy of the TIF5 gene, the eIF5 double-point mutants allowed only slow growth of this ΔTIF5 yeast strain, while the eIF5 hexamutant was unable to support cell growth and viability of this strain. These findings suggest that eIF5-eIF2β interaction plays an essential role in eIF5 function in eukaryotic cells.